2008
DOI: 10.3171/spi/2008/8/3/215
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of intraoperative neurophysiological monitoring during cervical spine surgery: a prospective analysis of 1055 consecutive patients

Abstract: Object Despite the growing use of multimodal intraoperative monitoring (IOM) in cervical spinal surgery, limited data exist regarding the sensitivity, specificity, and predictive values of such a technique in detecting new neurological deficits in this setting. The authors sought to define the incidence of significant intraoperative electrophysiological changes and new postoperative neurological deficits in a cohort of patients undergoing cervical surgery. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
96
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(99 citation statements)
references
References 26 publications
1
96
0
2
Order By: Relevance
“…Rather, spEMG was found to be relatively insensitive. 13,23 In the present study, intraoperative nerve root irritation, as identified by significant sustained bursts or, more often, trains of EMG neurotonic discharge, did not correlate with immediate postoperative deficits and had low sensitivity (20%) for detecting acuteonset deltoid muscle weakness. This is not at all surprising since intraoperative spEMG monitoring is not a test of functional neural integrity.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Rather, spEMG was found to be relatively insensitive. 13,23 In the present study, intraoperative nerve root irritation, as identified by significant sustained bursts or, more often, trains of EMG neurotonic discharge, did not correlate with immediate postoperative deficits and had low sensitivity (20%) for detecting acuteonset deltoid muscle weakness. This is not at all surprising since intraoperative spEMG monitoring is not a test of functional neural integrity.…”
Section: Discussionmentioning
confidence: 89%
“…18 Mechanical injury to the nerve root because of direct tractional force or trauma from a surgical instrument often leads to weakness in the acutely presented innervated muscle, and several studies have shown that tceMEP monitoring is highly effective for rapid identification of an evolving injury leading to weakness that is evident on waking from anesthesia. 1,5,10,12,13,20,22,23 Conversely, mechanisms, such as changes in perfusion and spinal cord shift, may be triggered hours or days after the conclusion of surgery. Since intraoperative neurophysiological monitoring in general and tceMEP surveillance in particular only reflect the status of the nervous system during surgery, it is not at all surprising that neither tceMEP nor spEMG monitoring were of any benefit in identifying C-5 nerve root changes that began long after surgery had ended.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We can hardly find a result of SSEP change for postoperative sensory deficit in terms of either quantitative or objective description of sensory change in the previous study [24,25]. At this retrospective study, we give up to measure postoperative sensory change as all that we could retrieve was subjective expression of patients about sensory change and vague dermatomal distribution.…”
Section: Predictability Of Mep and Ssep For Postoperative Motor Deficitmentioning
confidence: 99%
“…In IDEM and ED metastatic spinal tumour surgery, SSEP might reflect the functional integrity not only of dorsal column but also of motor tract as long as the spinal cord maintains its anatomical integrity throughout the surgery. However, reports of IOM for spinal tumour surgery is relatively rare and frequently mixed up with other spinal procedure, hence only a few of separate study of reporting IOM result of IDEM of ED metastatic spinal tumour surgery can be found [8][9][10].…”
Section: Introductionmentioning
confidence: 99%